mcr-1 Identified in Fecal Escherichia coli and Avian Pathogenic E. coli (APEC) From Brazil - Barbieri, Nicolle Lima; Pimenta, Ramon Loureiro; de Melo, Dayanne Araujo; Nolan, Lisa K.; de Souza, Miliane Moreira Soares; Logue, Catherine M. (Frontiers in Microbiology, 2021)
Colisitin-associated resistance in bacteria of food producing animals has gained significant attention with the mcr gene being linked with resistance. Recently, newer variants of mcr have emerged with more than 9 variants currently recognized. Reports of mcr associated resistance in Escherichia coli of poultry appear to be relatively limited, but its prevalence requires assessment since poultry is one of the most important and cheapest sources of the world’s protein and the emergence of resistance could limit our ability to treat disease outbreaks. Here, 107 poultry E. coli isolates were screened for mcr 1 - 9. The isolates were collected between April 2015 and June 2016 from broiler chickens and free-range layer hens in Rio de Janeiro, Brazil. All isolates were recovered from the trachea and cloaca of healthy birds and an additional two isolates were recovered from sick birds diagnosed with colibacillosis. All isolates were screened for the presence of mcr-1 to 9 using PCR and Sanger sequencing for confirmation of positive genes. Additionally, PFGE analysis, APEC virulence associated gene screening, replicon typing and antimicrobial resistance phenotype and resistance gene screening, were also carried out. The mcr-1 gene was detected in 62 isolates and the mcr-5 gene was detected in 3 isolates. PFGE analysis found that most of the isolates screened had unique fingerprints. Plasmid replicon types IncI2, FIB and B/O were found in 38, 36 and 34 % of the mcr positive isolates and were the most prevalent replicon types detected; tetA and tetB (32 and 26% respectively) were the most prevalent antimicrobial resistance genes detected and iutA, was the most prevalent APEC virulence associated gene, detected in 50% of the isolates. Approximately 32% of the isolates examined could be classified as APEC-like. This study has identified a high prevalence of mcr-1 in poultry isolates in Brazil, suggesting that animal husbandry practices could result in a potential source of resistance to the human food chain in countries where application of colistin in animal health is practiced. Emergence of the mcr gene and associated colisitin resistance in production poultry warrants continued monitoring from the animal health and human health perspective.